Review Article about Transformations of the concept of globalization: Scientific works from the 1990s to the present - Ali Omran Hussein; Haidar Eidan Kareem (Peerian Journals Publishing, 2025)
From the 1990s to the present, the term globalization has witnessed rapid developments in various scientific and intellectual fields. Globalization was viewed as an economic process whose primary focus was the integration of global markets and the strengthening of trade. Over time, this view has evolved to include diverse dimensions, including culture, society, and politics. Recent studies have shown that globalization affects not only the economy, but also cultural identity, domestic policies, and international relations. It has also been shown that globalization does not always lead to cultural or economic unification; rather, it can lead to significant disparities between countries and their social classes. This background article demonstrates that it has become a more complex concept intertwined with issues such as multiple identities, immigration policies, and the environment.
Keywords: social classes; Globalization; witnessed